2016
DOI: 10.14582/duzgef.709
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Attitudes, Views and Skills of Early Childhood Education Teacher Candidates on Science Education

Abstract: The aim of this study was to analyze the relationship between scientific process skills, attitudes toward science and science teaching and to uncover third and fourth class early childhood education (ECE) teacher candidates' views on science teaching. Mixed method research design was used in this study. Both of the quantitative and qualitative data was collected from the participants. The findings of the study showed that ECE teacher candidates' scientific process skills were at the medium level and their atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…As a result of the study, it was determined that pre-service preschool teachers had positive attitudes toward science teaching. Similarly, Aydın Şengül and Ertürk Kara (2016), Babaroğlu and Okur Metwalley (2018), Çınar (2013), Erden andSönmez (2011), andSönmez (2007) found that preschool teachers and pre-service teachers had positive attitudes towards science education. Raviv & Galili (2023) also found that most preschool teachers attach importance to teaching scientific content in kindergarten and that all teachers have positive attitudes towards science teaching in preschool education.…”
Section: Resultsmentioning
confidence: 96%
“…As a result of the study, it was determined that pre-service preschool teachers had positive attitudes toward science teaching. Similarly, Aydın Şengül and Ertürk Kara (2016), Babaroğlu and Okur Metwalley (2018), Çınar (2013), Erden andSönmez (2011), andSönmez (2007) found that preschool teachers and pre-service teachers had positive attitudes towards science education. Raviv & Galili (2023) also found that most preschool teachers attach importance to teaching scientific content in kindergarten and that all teachers have positive attitudes towards science teaching in preschool education.…”
Section: Resultsmentioning
confidence: 96%